Biblical pragmatism in the pandemic outbreak of Numbers 25:1–18: Towards an African paradigm - Ndoga, Sampson S. (HTS teologiese studies, 2021)
Numbers 25 presents a human crisis requiring swift leadership interventions to curb the plague. Leadership failure plays out on a number of levels before decisive and resolute interventions are taken. This passage shows a human-created crisis that somewhat parallels the coronavirus disease 2019 (COVID-19) outbreak and offers reflective pragmatic approaches taken to ensure immediate arresting of the pandemic and perhaps future curbing of a similar instigation.Contribution: Africa has always been known to respond rather belatedly to crises that cost human lives and also for waiting for solutions to come from elsewhere. How do we change that paradigm going forward and what does it mean for the analysis of biblical texts? African hermeneutical readings that take contextual issues rather seriously are utilised in this study.